Comparison of HIV prevention indicators among adolescent girls and young women in DREAMS and non-DREAMS intervention districts in Uganda - Norah Namuwenge; Derrick Kimuli; Rebecca N. Nsubuga; Timothy Sserunga; Sheila Nyakwezi; Jaffer Byawaka; Garoma Kena; Solome Sevume; Norbert Mubiru; Barbara Amuron; Daraus Bukenya (PLoS ONE, 2025)
In sub-Saharan Africa, a significant number of new human immunodeficiency virus (HIV) infections occur among adolescent girls and young women (AGYW). The 2023 Uganda Annual Spectrum estimates indicated that about one-third of all new HIV infections are among AGYW. In 2016, the Ministry of Health in partnership with the United States President’s Emergency Plan for AIDS Relief (PEPFAR) initiated the Determined, Resilient, Empowered, AIDS-Free, Mentored and Safe (DREAMS) program to reduce the vulnerability of AGYW to HIV by offering various direct and indirect HIV-related prevention services. These services influence the level of various HIV prevention indicators in the age group. This study aimed to compare these levels. The study was a secondary analysis of pooled Lot Quality Assurance Sampling (LQAS) survey data collected in DREAMS and non-DREAMS districts during 2021 and 2022. Fifteen HIV prevention indicators were independently compared between 8 DREAMS and 8 non-DREAMS districts. Chi-square tests were used to assess the significance in the differences. Of the 9,290 records of AGYW reviewed, 52.40% were of AGYW residing in DREAMS districts. Between DREAMS and non-DREAMS districts, significant differences in level of knowledge of HIV prevention methods (25.60% versus 14.63%, p < 0.001), condom use (58.99% versus 48.33%, p < 0.001), knowledge of HIV testing points (93.43% versus 92.38%, p = 0.049), having multiple sex partners (15.28% versus 10.11%, p < 0.001), condom use (58.99% versus 48.33%, p < 0.001), HIV testing (84.86% versus 82.00%, p < 0.001) and multiple sex partners (15.28% versus 10.11%, p < 0.001) among other indictors. AGYW in DREAMS districts had better outcomes for all indicators except multiple sex partners. Although this factor likely contributed to the initial selection of DREAMS-intervention districts, its persistence may continue to influence overall efforts towards the reduction of HIV prevalence. Moreover, this potentially mitigates the benefits from other better performing indicators.